2014
DOI: 10.2147/oajsm.s36528
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of eating disorders in female athletes

Abstract: Eating disorders are serious mental diseases that frequently appear in female athletes. They are abnormal eating behaviors that can be diagnosed only by strict criteria. Disordered eating, although also characterized as abnormal eating behavior, does not include all the criteria for diagnosing eating disorders and is therefore a way to recognize the problem in its early stages. It is important to identify factors to avoid clinical progression in this high-risk population. Therefore, the purpose of this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 50 publications
0
70
0
2
Order By: Relevance
“…Primary prevention efforts work to expand athlete knowledge about healthy eating, pathological eating behaviours and their consequences, and what to do if you or a teammate are thought to have an eating disorder 52 79. Athletes should be educated that dietary restriction and/or purging behaviour in pursuit of optimal weight and body composition will negatively impact sport performance and result in adverse health consequences.…”
Section: Preventionmentioning
confidence: 99%
“…Primary prevention efforts work to expand athlete knowledge about healthy eating, pathological eating behaviours and their consequences, and what to do if you or a teammate are thought to have an eating disorder 52 79. Athletes should be educated that dietary restriction and/or purging behaviour in pursuit of optimal weight and body composition will negatively impact sport performance and result in adverse health consequences.…”
Section: Preventionmentioning
confidence: 99%
“…At present, narrative reviews have been conducted to explore the efficacy of these programmes. For example, Coelho, Gomes, Ribeiro, and Soares () reported that interventions ( n = 6) aimed at preventing eating disorders in athletes were effective in changing female athletes' future intentions for eating and exercise behaviours immediately post‐intervention, with two studies reporting sustained effects at 9 months after the intervention. However, the incidence of eating disorder onset was not reduced (Coelho et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Coelho, Gomes, Ribeiro, and Soares () reported that interventions ( n = 6) aimed at preventing eating disorders in athletes were effective in changing female athletes' future intentions for eating and exercise behaviours immediately post‐intervention, with two studies reporting sustained effects at 9 months after the intervention. However, the incidence of eating disorder onset was not reduced (Coelho et al, ). In another review of athlete eating disorder prevention programmes ( n = 11; Bar, Cassin, & Dionne, ), it was reported that most interventions demonstrated promising findings in preventing or reducing eating psychopathology in athletes, with four studies reporting sustained intervention effects [2–6 weeks ( n = 2); 9–36 months ( n = 2)].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past nearly 30 years, an increasing number of preventive interventions addressing eating disorders and poor body image have been developed, with over a hundred approaches published in the literature (Coelho, Gomes, Ribeiro, & Soares, 2014;Holt & Ricciardelli, 2008;Levine, McVey, Piran, & Ferguson, 2012;Newton & Ciliska, 2006;Rodgers & Paxton, 2014;Stice, Becker, & Yokum, 2013;Stice, Shaw, Becker, & Rohde, 2008;Stice, Shaw, & Marti, 2007;Yager, Diedrichs, Ricciardelli, & Halliwell, 2013;Yager & O'Dea, 2008). These interventions have included universal, selective, and targeted prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…They have been designed for young children, adolescents, and adults in school and community settings and online. They have targeted self-esteem, body dissatisfaction, thin-ideal internalization, media literacy, healthful nutrition and physical activity, and other indicators (Coelho et al, 2014;Holt & Ricciardelli, 2008;Levine et al, 2012;Newton & Ciliska, 2006;Rodgers & Paxton, 2014;Stice et al, 2007Stice et al, , 2008Stice et al, , 2013Yager et al, 2013;Yager & O'Dea, 2008). Over 60 preventive interventions have been evaluated in controlled studies, the vast majority of which were efficacy trials (Stice et al, 2013).…”
Section: Introductionmentioning
confidence: 99%